2021
DOI: 10.2478/jcbtp-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Non-Performing Loan Determinants and Impact of COVID-19: Case of Bosnia and Herzegovina

Abstract: The aim of this paper is to investigate the determinants of the movement of non-performing loans in the banking sector of Bosnia and Herzegovina, as well as the impact of the COVID-19 pandemic on them. For this purpose, secondary data from the banking sector of BiH were used, over which a multi-regression analysis was performed. The variables non-performing loans, GDP, loan loss provision, and dummy variable COVID-19 were used in the analysis. The results of the analysis showed a significant influence of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…First, to our knowledge, it is the first work that studies the impact of the macroeconomic environment in Italy during the recent period. Several papers have analyzed this relationship in the U.S. (Ghosh 2015), European (Makri et al 2014;Rinaldi and Sanchis-Arellano 2006), Greek (Anastasiou et al 2019;Konstantakis et al 2016;Louzis et al 2012), France and Germany (Chaibi and Ftiti 2015), India (Gaur and Mohapatra 2020;Mishra et al 2021), and other world regions (Beck et al 2015;Espinoza and Prasad 2010;Hada et al 2020;Kjosevski et al 2019;Nkusu 2011;Tanasković and Jandrić 2015;Zheng et al 2020;Žunić et al 2021) contexts. However, only Bofondi and Ropele (2011) studied the relationship between macroeconomic variables and bad loans in the Italian context from 1990 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…First, to our knowledge, it is the first work that studies the impact of the macroeconomic environment in Italy during the recent period. Several papers have analyzed this relationship in the U.S. (Ghosh 2015), European (Makri et al 2014;Rinaldi and Sanchis-Arellano 2006), Greek (Anastasiou et al 2019;Konstantakis et al 2016;Louzis et al 2012), France and Germany (Chaibi and Ftiti 2015), India (Gaur and Mohapatra 2020;Mishra et al 2021), and other world regions (Beck et al 2015;Espinoza and Prasad 2010;Hada et al 2020;Kjosevski et al 2019;Nkusu 2011;Tanasković and Jandrić 2015;Zheng et al 2020;Žunić et al 2021) contexts. However, only Bofondi and Ropele (2011) studied the relationship between macroeconomic variables and bad loans in the Italian context from 1990 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…) although others described positive and significant link with them (Mahyoub, & Said, 2021;Beck, Piloiu, & Jakubik, 2015;Alexandri, & Santoso, 2015;Saba, Kouser, & Azeem, 2012). Furthermore, some of studies confirmed a insignificant association between GDP growth and non-performing loans (Žunić, Kozarić, & Dželihodžić, 2021;Dimitrios, Helen, & Mike, 2016;Tanasković, & Jandrić, 2015;Nor & Ahmad, 2015;Singh, Basuki, & Setiawan, 2021).…”
Section: Relationship Between Growth Of Gross Domestic Product On Nplsmentioning
confidence: 97%
“…The unemployment has the diversity of jobless comparative to the employees and dealings the amount of the workforce (Goensch, Gulyas, & Kospentaris , 2021;Huang et al, 2017). The crucial factors of NPLs nevertheless it additionally consumes a hyperlink towards the commercial enterprise and fiscal actions that have an effect on the call for of goods and offerings and in the end to enterprise ability to refund its credits (Žunić et al, 2021;Queglieriello, 2007;Singh et al, 2021).…”
Section: Impact Of Unemployment Rate On Nplsmentioning
confidence: 99%
“…On the other hand, banks carry out fairly gloom throughout melancholy and reduce borrowing and upward thrust distribution for lease lifeless or bounce worrying about elevated NPLs. Several research shows poor relation among NPLs and financial progress (Lubis & Mulyana, 2021;Prastowo & Usman, 2021;Mohaddes, Raissi, & Weber, 2017).Even though some researchers defined nice or widespread hyperlink between n them (Beck, Jakubik, & Piloiu, 2015;Alexandri & Santoso, 2015).However, few research showed a irrelevant affiliation among GDP increase and non-acting loans (Žunić et al, 2021;Dimitrios, Helen, & Mike, 2016;Nor, 2015;Singh et al, 2021). The end results, it briefs little deliverables boom of GDP decline capital redirection or borrowers' credit paying capacity on identical time as, equally better GDP motives towards upward thrust in NPLs.…”
Section: Impact Of Gdp On Nplsmentioning
confidence: 99%